2021
DOI: 10.4103/jfmpc.jfmpc_1462_20
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style in a rapidly developing country

Abstract: Objective: To investigate the different styles of parenting in the State of Qatar, a country that is considered a cosmopolitan hub with rapid development. Materials and Methods: A cross-sectional study was conducted at Sidra Medicine, the only tertiary pediatric hospital in Qatar. Parents of children 3–14 years old were offered a questionnaire. Results: A total of 114 questionnaires were completed (response rate = 95%). Approximately 65% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This lack of parent clarity regarding what constitutes developmentally appropriate skills at different life stages carries significant detrimental implications. Parents' ability to recognize red flags and abnormal delays hinges on internalized reference intervals for when children should achieve functional developmental capacity in areas like mobility, speech, or socialization [ 11 , 12 ]. Misconceptions regarding age-appropriate competence can heighten caregiver anxiety and precipitate premature interventions [ 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of parent clarity regarding what constitutes developmentally appropriate skills at different life stages carries significant detrimental implications. Parents' ability to recognize red flags and abnormal delays hinges on internalized reference intervals for when children should achieve functional developmental capacity in areas like mobility, speech, or socialization [ 11 , 12 ]. Misconceptions regarding age-appropriate competence can heighten caregiver anxiety and precipitate premature interventions [ 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening pediatric partnerships through clinical policies prioritizing detailed, repeated development data exchange could help bridge consciousness disconnects [ 12 ]. Standardized screening questionnaires for routinely tracking maturation across domains beyond infancy could enhance detection capacities [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two features of the Arabic (younger and culturally distinct) sample may account for that issue: first, acquiescence has been found in younger kids responding to multiple-choice questions (e.g., Suárez-Álvarez et al, 2018), and second, higher acquiescence levels were observed in responses of participants from cultures with a lower level of democratization (He et al, 2014). Parenting practices in Qatar, where obedience to authority is esteemed (Hendaus et al, 2021), may contribute to this response pattern. Participants might perceive the researcher as a figure of authority, potentially elevating acquiescence levels within our study.…”
Section: Construct Validity Of A-ipdwamentioning
confidence: 99%